Political Dynamics of Islamic Law in the Reform Era: A Study of the Response of Muhammadiyah Cadres in Central Kalimantan - Sukti, Surya; Warsito, Tulus; Qodir, Zuly; Jubba, Hasse (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2022)
This study aims to make a scientific contribution to the development of Islamic studies and the politics of Islamic law, especially democracy from the perspective of Muhammadiyah cadres in Central Kalimantan. This research was conducted using empirical research methods with a qualitative-descriptive approach. The data collection technique used was interviewing key information, namely Muhammadiyah cadres and literature studies in the form of writing related to the discussion. The results of the study show that the development of Indonesian democracy in the Reform Era, 2005 to 2019 as understood is quite dynamic, this can be seen from issues such as; general elections, human rights and gender, terrorism and democracy, then the response of Muhammadiyah cadres to democracy; (1) democracy is compatible or in line with Islamic values; and (2) these three subjects are more concerned with procedural democracy than substantive democracy, such as holding general elections and national and regional political recruitment, which must be corrected and improved.